2020
DOI: 10.1038/s41388-020-1362-9
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo pathway oncoprotein YAP promotes melanoma cell invasion and spontaneous metastasis

Abstract: Melanoma is a deadly form of skin cancer that accounts for a disproportionally large proportion of cancer-related deaths in younger people. Compared to most other skin cancers, a feature of melanoma is its high metastatic capacity, although molecular mechanisms that confer this are not well understood. The Hippo pathway is a key regulator of organ growth and cell fate that is deregulated in many cancers. To analyse the Hippo pathway in cutaneous melanoma, we generated a transcriptional signature of pathway act… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 64 publications
4
84
0
Order By: Relevance
“…This suggests that YAP activity can compensate for loss of BRAF V600E signaling. Given MAPK inhibitor resistance remains a significant component of treatment failure, our data suggests that co-targeting MAPK and YAP-TEAD signaling could simultaneously prevent resistance (69) and decrease melanoma cell viability (32,77).…”
Section: ! Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that YAP activity can compensate for loss of BRAF V600E signaling. Given MAPK inhibitor resistance remains a significant component of treatment failure, our data suggests that co-targeting MAPK and YAP-TEAD signaling could simultaneously prevent resistance (69) and decrease melanoma cell viability (32,77).…”
Section: ! Discussionmentioning
confidence: 99%
“…It is not known if Hippo pathway activation contributes to the growth arrest of nevus melanocytes. Moreover, while Hippo pathway inactivation has been suggested to promote cutaneous melanoma growth and invasion (30)(31)(32), it remains unknown whether Hippo inactivation is sufficient to induce cutaneous melanoma initiation and/or progression. Here, we use a combination of in vitro and in vivo model systems to examine the role of the Hippo tumor suppressor pathway in restraining melanoma development.…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous metastasis status in in vivo models was evaluated by human mitochondrial IHC of liver, lung and lymph nodes 50 . Briefly, slides were de-waxed and antigen retrieval was performed in a pressure cooker at 125°C for 3 min employing an Antigen Retrieval solution (Dako, pH6 for EZH2, pH9 for Anti-human Mitochondrial Antibody).…”
Section: Methodsmentioning
confidence: 99%
“…In YAP1-transformed MIHA HCC cells, the knockdown of Axl interfered with migration and invasion and reduced the metastatic potential of the cells [16]. Another study done using melanoma cancer cell lines showed that Axl is an important gene in YAP-induced melanoma cell invasion [45].…”
Section: Invasion and Migrationmentioning
confidence: 97%